2017
DOI: 10.1093/ckj/sfx030
|View full text |Cite
|
Sign up to set email alerts
|

Rare genetic variants in Shiga toxin-associated haemolytic uraemic syndrome: genetic analysis prior to transplantation is essential

Abstract: We present a case of haemolytic uraemic syndrome (HUS) in a 16-year-old female with serological evidence of acute Escherichia coli O157:H7 infection. She progressed to established renal failure and received a deceased donor kidney transplant. Shiga toxin–associated HUS (STEC-HUS) does not recur following renal transplantation, but unexpectedly this patient did experience rapid and severe HUS recurrence. She responded to treatment with the terminal complement inhibitor eculizumab and subsequent genetic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Still, when we focused our analysis on very rare pathogenic variants with minor allele frequency ,0.1%, we showed that such very rare pathogenic variants were associated with a fivefold higher risk of developing Shiga toxin-positive HUS. Thus, although Shiga toxin-associated HUS is mostly driven by the infectious agent, our study highlights that in rare cases, genetic abnormalities may contribute to complement activation in Shiga toxin-associated HUS, consistent with published data (9,10,(20)(21)(22)(23)(24)(25)(26)(27)(28). However, our study did not include patients with Shiga toxin infection who did not develop HUS (a study difficult to complete outside of large epidemics) and thus cannot prove the role of genetics in the risk of developing HUS after Shiga toxin infection.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Still, when we focused our analysis on very rare pathogenic variants with minor allele frequency ,0.1%, we showed that such very rare pathogenic variants were associated with a fivefold higher risk of developing Shiga toxin-positive HUS. Thus, although Shiga toxin-associated HUS is mostly driven by the infectious agent, our study highlights that in rare cases, genetic abnormalities may contribute to complement activation in Shiga toxin-associated HUS, consistent with published data (9,10,(20)(21)(22)(23)(24)(25)(26)(27)(28). However, our study did not include patients with Shiga toxin infection who did not develop HUS (a study difficult to complete outside of large epidemics) and thus cannot prove the role of genetics in the risk of developing HUS after Shiga toxin infection.…”
Section: Discussionsupporting
confidence: 92%
“…However, the role of hereditary complement abnormalities needs to be confirmed by a large international study. Finally, considering our data and prior case reports of STEC infection unmasking complement deficiency, genetic screening does not appear justified for all patients with postdiarrheal HUS, but should be considered in patients with a fulminant course to death or ESKD (19,20,22,27), progression to ESKD within ,3 years (patient 1, Table 5), a family history of HUS (23) (patient 6, Table 5), relapse of HUS (21,23,26), or post-transplant recurrence (22,27).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, all individuals with TMA should be investigated for STEC-HUS (Figure 3). Rarely, complement gene mutations are detected, and in these cases the clinical picture is unusually severe (13,65). In STEC-HUS resulting in ESRD, it is recommended to screen for mutations before transplantation.…”
Section: Stec-husmentioning
confidence: 99%
“…In addition to infection complications, other concerns may emerge as use of complement-inhibiting therapy in clinical practice increases. Eculizumab-associated hepatotoxicity has been reported in children [ 19 ], and glomerular deposition of eculizumab in individuals with C3 glomerulopathy (C3G) [ 20 ], though not complement-mediated aHUS [ 21 ], has been reported although the long-term clinical consequences are as yet unclear.…”
Section: Complementmentioning
confidence: 99%